1996
DOI: 10.1242/jcs.109.11.2715
|View full text |Cite
|
Sign up to set email alerts
|

Talin contains three actin-binding sites each of which is adjacent to a vinculin-binding site

Abstract: We have determined the sequence of chicken talin (2,541 amino acids, M(r) 271,881) which is very similar (89% identity) to that of the mouse protein. Alignments with the Caenorhabditis elegans and Dictyostelium discoideum talin sequences show that the N- and C-terminal regions of the protein are conserved whereas the central part of the molecule is more divergent. By expressing overlapping talin polypeptides as fusion proteins, we have identified at least three regions of the protein which can bind F-actin: re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…Another major role of talin R7R8 is to bind actin (Hemmings et al, 1996), and TLNRD1 has previously been shown to bind actin (Gingras et al, 2010). Using a high-speed cosedimentation assay, we confirmed that TLNRD1-FL interacts with actin filaments (Fig.…”
Section: Tlnrd1 Retains the Functionality Of Talin R7r8supporting
confidence: 73%
See 1 more Smart Citation
“…Another major role of talin R7R8 is to bind actin (Hemmings et al, 1996), and TLNRD1 has previously been shown to bind actin (Gingras et al, 2010). Using a high-speed cosedimentation assay, we confirmed that TLNRD1-FL interacts with actin filaments (Fig.…”
Section: Tlnrd1 Retains the Functionality Of Talin R7r8supporting
confidence: 73%
“…Talin R7R8 is emerging as a major signaling hub, linking diverse cytoskeletal elements together (Goult et al, 2018). It forms part of a major actin-binding site (actin-binding site 2 [ABS2]) that spans R4-R8 (Atherton et al, 2015;Kumar et al, 2016;Hemmings et al, 1996). Talin R7R8 also binds to multiple other ligands, many of which contain leucine-aspartate motifs (LD motifs; Alam et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in the nascent adhesions formed at the onset of spreading, kindlin was directly binding paxillin; paxillin was then recruiting FAK to these nascent adhesions. On the other hand, the important role of vinculin in several processes in the integrin-talin-FAK adhesion complex appears to be relevant mostly at the mature focal adhesion stage (Hemmings, Rees, Ohanian, Bolton, Gilmore, Patel, Priddle, Trevithick, Hynes, and Critchley, 1996, Margadant et al, 2011, Yao, Goult, Chen, Cong, Sheetz, and Yan, 2014, and we believe its role is to bind different adhesion complexes into a dense focal adhesion raft.…”
Section: Discussionmentioning
confidence: 85%
“…LD-containing proteins that bind talin in this way include RIAM (Goult et al, 2013b), KANK family proteins (Bouchet et al, 2016), CDK1 (Gough et al, 2021), DLC1, paxillin (Zacharchenko et al, 2016) and tensin (Atherton et al, 2021 preprint). LD-independent folded rod binders include F-actin (Hemmings et al, 1996), synemin (Sun et al, 2008), moesin (Beaty et al, 2014) and the talin F3 domain that mediates autoinhibition (Goksoy et al, 2008;Goult et al, 2009). Unfolded (1) rod binders Currently only vinculin has been identified as binding to talin in its unfolded state.…”
Section: The Talin Head Domainmentioning
confidence: 99%
“…additional cytoskeletal linkages (Ciobanasu et al, 2018;Hemmings et al, 1996), but its function is not well understood. Of these, vinculin is best characterized and can bind to the 11 vinculin binding sites (VBSs) distributed throughout the talin rod (Gingras et al, 2005).…”
Section: The Talin Head Domainmentioning
confidence: 99%